Analisis Komunikasi Krisis pada Kementerian Agama dalam Penyelenggaraan Ibadah Haji 2025 - Fakhrur Rozi; Nazil Mumtaz al-Mujtahid (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
This study analyzes the crisis communication strategies employed by the Indonesian Ministry of Religious Affairs (Kemenag) during the 2025 Hajj pilgrimage, which was marked by logistical and administrative problems, and their impact on public perception. The urgency of this research lies in the need for transparent and rapid communication to restore public trust during institutional crises. Using a qualitative case study approach, the study draws on press releases, social media statements, and media observations of Kemenag’s responses. Situational Crisis Communication Theory (SCCT) and Image Repair Theory are applied to examine the ministry’s communication strategies. The findings show that public sentiment toward the 2025 Hajj administration was predominantly negative, with complaints concerning transportation, accommodation, and bureaucratic procedures. Kemenag’s responses tended to emphasize image management through deny and diminish strategies, supported by clarifications that lacked concrete solutions. SCCT analysis indicates that rebuild and reinforce strategies were ineffective without corrective actions. Image Repair analysis also reveals insufficient restoration efforts due to the absence of compensation or strong justification. The study proposes the T-REACT crisis communication model.